IMPROVING STUDENTS’ WRITING ABILITY IN NARRATIVE TEXT USING PICTURE SERIES - Putri Indah Sari; Thathit Manon Andini; Ida Feri Prihatin; Bayu Hendro Wicaksono (IKIP Siliwangi, 2024)
Writing is one of the language skills in learning English that is closely related to the text and must be mastered by high school students. One of the texts is a narrative text which focuses on entertaining the readers. This research aimed to analyze the improvements in students’ writing ability to write narrative text by using picture series. The research method is categorized as classroom action research which was conducted in two cycles. The student’s writing ability is examined by checking five aspects of writing which was contents, organization, vocabulary, language use, and mechanics. This study found that the use of picture series in learning narrative text has had a positive impact on improving students' writing ability. Regarding the analysis of students' work from pre-cycle until cycle II, the data indicated that the use of picture series has an impact to develop students’ writing through the improvement of the mean score in contents, organizations, vocabulary, language use, and mechanics.